Stuck in This Place - Solomon, Janice (Homœopathic Links, 2015)
A young woman of 18, dealing with amenorrhoea since puberty, starts homeopathic treatment in 2010. She describes herself as being ‘stuck in this place’. The absence of her menstrual cycles creates stress emotionally and mentally. Improvements with the mineral remedy Silica helped, but treatment shifted most dramatically with the author's introduction to the Joshis' work on finding animal remedies. The simple use of questions about the client's likes in nature and animals opened up new information that clarified the most healing remedy source. The themes of animals, and more specifically the subkingdom of insects, became clear and apparent with the Joshi case taking questions. The unusual description of ‘light through trees’ and dislike of ants indicated Formica rufa as a curative remedy. The client has had regular menstrual cycles for over 2½ years with the use of Formica rufa.
Keywords: Stuck; Amenorrhoea; Silica; Formica rufa